(untitled) (Journal of Entrepreneurship and Business, 2024)
The objective of this study is to assess the effectiveness of a Science, Technology, Engineering, and Mathematics (STEM) initiative in attaining the objectives specified in Malaysia’s Education Development Plan (PPPM) 2013- 2025. This study emphasises the significance of incorporating STEM education in Malaysia, with a specific focus on its contribution to the development of analytical thinking, problem-solving abilities, and creative thinking among the youth. The focus of this study is specifically directed towards the country of Malaysia. This underscores the need to employ a comprehensive and interdisciplinary methodology while developing a strategy The present study involves the analysis of replies provided by participants enrolled in a STEM education program. The dataset comprises demographic data of students spanning from Forms 1 to 5, together with information pertaining to their levels of interest in STEM. The analysis of post-program surveys indicates a notable increase in agreement and high agreement, particularly in the subjects of Mathematics and Engineering. This trend suggests an increasing level of enthusiasm among individuals toward pursuing careers in the STEM disciplines. A large majority (78%) of participants said the program influenced their future STEM interests, especially in engineering.